The Application Of The Naïve Bayes Method In Diagnosing Heart Disease In Medan City - Septia Handayani; Fibri Rakhmawati (Universitas Wiralodra, 2025)
This study applies the Naïve Bayes method to diagnose coronary heart disease (CHD) in Medan City. This quantitative study uses secondary data from Malahayati Islamic Hospital, including independent variables (age, gender, smoking, blood pressure, family history) and dependent variables (CHD status). The data are divided into training data (90%) and testing data (10%). Despite the high accuracy, further research with larger and more diverse data is needed to validate these findings. The Naïve Bayes method has proven potential as an aid in the early diagnosis of CHD.